Daily life in ancient Rome : a sourcebook - Harvey, Brian K. (Indianapolis : Focus, an imprint of Hackett Publishing Company, Inc., 2016)
"This book is first and foremost about the Romans themselves: who they were, how they defined themselves, where they lived and what they did to live their lives. ... The current volume is a sourcebook, a collection of evidence from the Roman world in the form of primary sources: texts, artifacts, and architecture that were created by the Romans themselves." --preface.
A short history of the Empire -- The monarchy -- The early Republic -- The fall of the Republic -- The Empire -- The late Empire -- The structure of society -- Citizenship -- Defining the aristocracy: birth and wealth -- The poor -- Virtue and vice -- Roman virtue -- Exemplary virtues -- Social versus legal constraints -- Moral decay and its ramifications -- Examples of vice -- The family -- The familia and the paterfamilias -- Marriage -- Divorce, adultery and marital problems -- Women -- The traditional view of Roman women -- Male control of women -- Negative depictions of women -- Empowered women -- Children -- Constraints on population growth -- Birth and infancy -- Childhood -- Education -- Roman pets -- Slaves -- The institution of slavery -- Rural slaves -- Urban slaves -- The treatment of slaves -- Freedmen -- Three cities in Italy -- Rome -- Ostia -- Pompeii -- The urban experience -- Literary scenes of busy streets -- Graffiti from Pompeii -- Housing -- The parts of a Roman aristocratic house -- Apartments -- Country villas -- Neighborhoods, water, sanitation, and the grain supply -- Neighborhoods -- Aqueducts and the water supply -- Sewers and latrines -- The grain supply -- The daily routine -- Descriptions of the day's routine -- Waking up -- The Ornatrix -- The morning salutatio -- Business and occupations -- Workers -- Shops and workshops -- The fuller -- Religion -- The Roman gods -- Cult and worship -- Priests -- Temples -- Sacrifice and ritual -- The growth of Christianity -- The army -- The army of the republic -- The army of the imperial period -- Life in the country -- Glimpses of country life -- The rustic labor force -- The baths -- The bath complex -- The bathing ritual -- Dinner parties -- The Triclinium -- Invitations to aristocratic dinners -- Luxurious dinner parties -- Bars and inns -- Eating and drinking establishments -- Inns -- Public entertainment: the theater and circus -- The theater -- The circus and chariot racing -- Public entertainment: the amphitheater -- The history of amphitheatrical games -- The amphitheater -- Gladiators -- Gladiatorial combat -- Glossary -- Works quoted.
Includes bibliographical references (pages 331-341) and index.
Keywords: Civilization; Rome (Empire); Ancient Rome